The Association Between Vitamin D Status and Glycemic Control in Children and Adolescents with Type 1 Diabetes - Hamza Alasbily; Sana Abdalrahman; Mona Netfa; Adela Elemmami; Abdolkader Aldebani (AlQalam Journal of Medical and Applied Sciences, 2024)
Low vitamin D levels are common in children and adolescents with type 1 diabetes. Although a link between vitamin D status and glycemic control is suggested, the direct association with poor control is unclear. This study assessed the prevalence of low vitamin D (deficiency and insufficiency) and its relationship with HbA1c in youth with type 1 diabetes. A cross-sectional study at Benghazi Medical Center, Libya, from June to September 2018 included 63 patients (33 females, 30 males), aged 6-18 years. Data on socio-demographics, HbA1c, and vitamin D levels were collected. Vitamin D levels were categorized as deficient (<10 ng/ml), insufficient (10-19 ng/ml), or sufficient (≥20 ng/ml). Glycemic control was classified as good (HbA1c ≤ 7.5%), fair (7.6%-8.5%), or poor (≥8.6%). Analysis using SPSS version 18 showed patients had a mean age of 12 years (±3.9), BMI of 19.18 kg/m² (±3.70), diabetes duration of 4.90 years (±3.03), average HbA1c of 10.10% (±2.5), and mean vitamin D level of 17.70 ng/ml (±10.8). Deficient vitamin D was found in 27% of patients, with 36.5% insufficient and 36.5% sufficient. A weak negative correlation (r= -0.112, p=0.38) was observed between 25-hydroxyvitamin D and HbA1c. Low vitamin D levels, including deficiency and insufficiency, were prevalent in youth with type 1 diabetes. However, vitamin D status did not significantly impact glycemic control in this study. ينتشر انخفاض مستوى فيتامين د بين الأطفال والمراهقين المصابين بداء السكري من النوع الأول. على الرغم من تراكم الأدلة التي تدعم وجود علاقة بين حالة فيتامين د والسيطرة على نسبة السكر في الدم لدى مرضى السكري، لا يزال من غير الواضح ما إذا كان انخفاض مستوى فيتامين د مرتبطًا مباشرة بسوء السيطرة على نسبة السكر في الدم في هذه الفئة من المرضي. هدفت هذه الدراسة إلى تقييم انتشار انخفاض حالة فيتامين د بين مرضي السكري من النوع الاول من الاطفال والمراهقين والتحقيق في العلاقة المحتملة بين 25-هيدروكسي فيتامين د (مؤشر وظيفي لحالة فيتامين د) والقدرة علي التحكم في السكري . أُجريت هذه الدراسة المقطعية في عيادة الأطفال بمركز بنغازي الطبي، بنغازي-ليبيا، بين يونيو وسبتمبر 2018. شملت الدراسة ثلاثة وستين طفلاً ومراهقًا مصابين بداء السكري من النوع الأول (33 أنثى، 30 ذكرًا) تتراوح أعمارهم بين 6 إلى 18 عامًا. تم جمع البيانات الاجتماعية والديموغرافية ومستوي فيتامين د ومعدل السكر التراكمي للمرضي حيث اعتبر مستوي فيتامين د < 10 نانو جرام/مل نقصا والمستوي بين م 10-19 نانو جرام/مل كمستوي غير كافي و ≥20 نانوجرام/مل كمستوي الكفاية. تم تصنيف التحكم في مستوى الجلوكوز في الدم إلى ثلاث فئات: جيد (قيمة ≤ 7.5%)، متوسط (7.6%-8.5%)، أو ضعيف (≥8.6%). تم جمع البيانات وادخالها وتحليلها احصائيا. كان متوسط عمر المرضى 12 عامًا (±3.9)، ومؤشر كتلة الجسم 19.18 كجم/م² (±3.70)، ومدة الإصابة بالسكري 4.90 سنوات (±3.03). كان متوسط مؤشر التحكم بالسكر التراكمي 10.10% (±2.5)، ومتوسط مستوى فيتامين د 17.70 نانوجرام/مل (±10.8). تم العثور على نقص فيتامين د في 27% من المرضى، و36.5% كانت لديهم مستويات غير كافية، بينما كانت مستويات الفيتامين كافية في 36.5% من المشاركين . لوحظت علاقة سلبية ضعيفة بين 25-هيدروكسي فيتامين د ومؤشر التحكم بالسكر التراكمي. بشكل عام، كانت مستويات فيتامين د المنخفضة، بما في ذلك النقص وعدم الكفاية، منتشرة بين الاطفال والمراهقين المصابين بالسكري من النوع الاول. ومع ذلك، لم يكن لحالة فيتامين د تأثير كبير على التحكم في مستوى السكري في الدم في هذه الدراسة